Effect of posterior pericardiotomy in cardiac surgery: A systematic review and meta-analysis of randomized controlled trials - Soletti, Giovanni Jr; Perezgrovas-Olaria, Roberto; Harik, Lamia; Rahouma, Mohamed; Dimagli, Arnaldo; Alzghari, Talal; Demetres, Michelle; Bratton, Brenden A.; Yaghmour, Mohammad; Satija, Divyaam; Lau, Christopher; Girardi, Leonard N.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Posterior pericardiotomy (PP) has been shown to reduce the incidence of pericardial effusion and postoperative atrial fibrillation (POAF) after cardiac surgery. However, the procedure and the totality of its effects are poorly known in the cardiac surgery community. We performed a study-level meta-analysis of randomized controlled trials (RCTs) to evaluate the impact of PP in cardiac surgery patients. Methods A systematic literature search was conducted on three medical databases (Ovid MEDLINE, Ovid Embase, Cochrane Library) to identify RCTs reporting outcomes of patients that received a PP or no intervention after cardiac surgery. The primary outcome was the incidence of POAF. Key secondary outcomes were operative mortality, incidence of pericardial and pleural effusion, cardiac tamponade, length of stay (LOS), pulmonary complications, amount of chest drainage, need for intra-aortic balloon pump, and re-exploration for bleeding. Results Eighteen RCTs totaling 3,531 patients were included. PP was associated with a significantly lower incidence of POAF (odds ratio [OR] 0.45, 95% confidence interval [CI] 0.32-0.64, P<0.0001), early (OR 0.18, 95% CI 0.10-0.34, P<0.0001) and late pericardial effusion (incidence rate ratio 0.13, 95% CI 0.06-0.29, P<0.0001), and cardiac tamponade (risk difference -0.02, 95% CI -0.04 to -0.01, P=0.001). PP was associated with a higher incidence of pleural effusion (OR 1.42, 95% CI 1.06-1.90, P=0.02), but not pulmonary complications (OR 0.82, 95% CI 0.56-1.19; p=0.38). No differences in other outcomes, including operative mortality, were found. Conclusions PP is a safe and effective intervention that significantly decreases the incidence of POAF and pericardial effusion following cardiac surgery.